On‐chip near‐infrared absorption enhancement of liquid water using chalcogenide waveguide with silver island film. Issue 5 (10th December 2021) - Pi, Mingquan; Ji, Jialin; Zheng, Chuantao; Li, Xiuying; Zhao, Huan; Peng, Zihang; Lang, Jiaming; Zhang, Yu; Wang, Yiding; Tittel, Frank K.
Abstract: For optical waveguide sensor based on evanescent field, the limitation of the light intensity caused by the waveguide loss leads to a short interaction length. Increasing external confinement factor can increase absorbance to overcome this problem. A chalcogenide waveguide was proposed for water absorption measurement, whose core layer was fabricated by lift‐off method. Silver island film was fabricated on the surface of core layer by oblique angle deposition method, which was used to introduce surface‐enhanced infrared absorption (SEIRA) effect. The surface morphology of the metal island structure with different thicknesses were characterized. Liquid water was used as the analyte. The sensor with 1.8 nm thick silver island film had the largest absorbance enhancement factor (>2.1) with an increased waveguide loss of only 1 dB/cm. The SEIRA effect using metal island film can also be used in slot waveguide or suspended waveguide to further achieve better performance.